ДИСКУРС КАК КОНСТРУКТИВНЫЙ ПРИНЦИП ПОСТМОДЕРНИЗМА - ГОЛОВАНОВ, Б. Д. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science")
Статья посвящена одной из ключевых категорий постмодернизма «дискурсу». Эта категория в структуре постмодернизма замещает понятие «идеология» и претендует на роль конструктивного принципа философии постмодернизма. Исследуются различные интерпретации понятия дискурс, характерные для представителей философии постмодернизма. Ключевые слова: дискурс, идеология, постмодернизм. Голованов Б. Д. ДИСКУРС ЯК КОНСТРУКТИВНИЙ ПРИНЦИП ПОСТМОДЕРНІЗМУ Стаття присвячена одній з ключових категорій постмодернізму «дискурсу». Ця категорія в структурі постмодернізму заміщає поняття «ідеологія» і претендує на роль конструктивного принципу філософії постмодернізму. Досліджуються різні інтерпретації поняття дискурс, характерні для представників філософії постмодернізму. Ключові слова: дискурс, ідеологія, постмодернізм. Golovanov B. D. DISCOURSE AS A CONSTRUCTIVE PRINCIPLE OF THE POSTMODERNISM Article is devoted to one of the key categories of postmodern "discourse." This category is within the structure of postmodernism replaces the concept of "ideology" and claim to be the constructive principle of the philosophy of postmodernism. Explores different interpretations of the concept of discourse is typical for the representatives of the philosophy of postmodernism. Key words: discourse, ideology, postmodernism.